Charge and spin currents in the ballistic SNS Josephson junction between p-wave superconductors - Rashedi, G.; Rahnavard, Y.; Kolesnichenko, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Charge and spin transport properties of a clean TS–N–TS Josephson junction (triplet superconductor-normal metal-triplet superconductor) are studied using the quasiclassical Eilenberger equation for Green's function. Effects of thickness of normal layer between superconductors on the spin and charge currents are investigated. The effect of a misorientation between triplet superconductors which creates the spin current is the main subject of this paper. It is shown that for some values of phase difference between superconductors the spin current exists in the absence of charge current and vice versa.